2012
DOI: 10.1183/09031936.00189911
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis-related deterioration of lung function after extracorporeal membrane oxygenation

Abstract: The aim of the study was to assess lung function longitudinally after neonatal extracorporeal membrane oxygenation (ECMO), and to identify any effects of diagnosis and perinatal characteristics.121 neonatal ECMO-treated children (70 with meconium aspiration syndrome, 20 congenital diaphragmatic hernia and 31 with other diagnoses) performed a total of 191 lung function measurements at 5, 8 and/or 12 yrs. We assessed dynamic and static lung volumes, reversibility of airway obstruction and diffusion capacity.Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…To our knowledge, only our group has previously reported on longitudinal lung function in children and young adults who survived CDH . In a study of ECMO‐treated patients with small numbers of CDH patients, lung function had deteriorated over time at school age .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only our group has previously reported on longitudinal lung function in children and young adults who survived CDH . In a study of ECMO‐treated patients with small numbers of CDH patients, lung function had deteriorated over time at school age .…”
Section: Discussionmentioning
confidence: 99%
“…6,8,20,21,33 The study populations of Haliburton et al 21 To our knowledge, only our group has previously reported on longitudinal lung function in children and young adults who survived CDH. 6,7 In a study of ECMO-treated patients with small numbers of CDH patients, lung function had deteriorated over time at school age. 7 In a cohort born before ECMO was introduced in the Netherlands (1991), mild airflow obstruction had deteriorated from childhood to young adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms our earlier observations in 35 eightyear-old CDH survivors who had longterm problems with motor function and concentration, even when they had not been treated with ECMO. 21 A high presence of CLD and increased airflow obstruction that deteriorates over time 22 may contribute to poor motor function performance in these CDH patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we showed that children born with major anatomical foregut anomalies and/or treated with ECMO are at risk for long‐term respiratory morbidity, reduced exercise capacity, and even deterioration of exercise capacity . In this RCT, we aimed to evaluate whether these children's exercise capacity can be improved.…”
Section: Perspectivementioning
confidence: 99%
“…Children born with major anatomical foregut anomalies, for example, congenital diaphragmatic hernia (CDH), esophageal atresia (EA), and congenital pulmonary airway malformation (CPAM), may require treatment with extracorporeal membrane oxygenation (ECMO) for cardiorespiratory failure. Also, neonates without congenital anatomical anomalies (CAA) may require ECMO, for example, meconium aspiration syndrome or sepsis …”
Section: Introductionmentioning
confidence: 99%